PENGUJIAN PROTOTYPE MESIN INJKESI PLASTIC MOLDING MANUAL DOUBLE BARREL KAPASITAS 5 TF - Matahelumual, Marselino; Muslimin, Muslimin (Jurnal Rekayasa Mesin, 2024)
The plastic injection method is a technique for producing plastic products with different properties and dimensions. The product is made from a combination of materials in the form of particle plastic material, which is used in this study is a thermoplastic polypropylene (PP) type material, this material becomes soft when heated and vice versa becomes hard again when cooled. The conversion of these raw materials is only physical and not chemical conversion, so these raw materials can be recycled if necessary. Plastic injection must meet the requirements such as shape, size and not have defects in the final product injection results such as short shots defects, flashing defects, sink marks defects and flow mark defects and weld lines. The process of injection of plastic products requires optimal parameter settings, namely, heating temperature, melting point, cooling, residence time and injection speed. So that in testing using a manual double barrel plastic injection molding machine with a capacity of 5 tf (5 ton-force = 5000 kg, calming force on molding), it is mandatory to get proper temperature variations and optimal parameter settings, in order to get perfect injection results, in the study The method used is an experimental method consisting of temperature variations of 160 °C, 180 °C and 200 °C which were carried out three times for each temperature variation. After conducting research, we found perfect product results after cleaning, that is, at a temperature test of 180 °C, because only minor flashing defects occurred in the final product. Low and high heater temperature settings, greatly affect the final product.